TDMA multiplexing of ATM cells in a residential access SuperPON. - Angelopoulos, J.D (IEEE Journal on selected areas in communications)
Time division multiple access (TDMA) multiplexing of ATM cells from thousands of residential customers toward the common feeder of a passive optical network (SuperPON) tree obviates the need for an equal number of optical line terminations (OLTs). All upstream transmissions converge by means of the passive splitters/combiners to just one OLT unit which serves all by time sharing. The ability to reach such a high splitting ratio became possible by the development of bursty mode optical amplifiers (OAs). In addition, OAs make possible a 100-km-long feeder which can bypass the local exchange into the first core switch, bringing further savings to both initial and running costs. These techniques allow SuperPONs to lower the access cost per customer, holding for the promise of ushering into domestic local loops the photonics revolution which has already transformed the transmission plant. These savings, however, can only be realized under the assumption that the system can accept high loading before exceeding the limits of quality of service (QoS) requirements and without distorting the egress traffic in a way that jeopardizes the statistical estimates on which ATM connection acceptance was based. Solutions to the problem of traffic arbitration, respecting the idiosyncrasies of each traffic class and suitable for fast implementation, are offered